(SJ APASXYQJ X]P SALEL]Ps - Cole M; Cole S.R; Lightfoot C. (Gutenberg, 2014)
(SAPYU]SLPJ APASXYQJ BUFZLMJ JNLMLA SU]XJ SALELMJ JNLMLA OFVJ SALELMJ JNLMLA FZJBFLA MRLP]PLMJ PRJORVYPJ VYPALVKJOAXLMJ PRJORVYPJ V]OAXLMJ APASXYQJ DP]VXLMJ APASXYQJs
(SAPYU]SLPJ APASXYQJ BUFZLMJ JNLMLA SU]XJ SALELMJ JNLMLA OFVJ SALELMJ JNLMLA FZJBFLA MRLP]PLMJ PRJORVYPJ VYPALVKJOAXLMJ PRJORVYPJ V]OAXLMJ APASXYQJ DP]VXLMJ APASXYQJs